Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =25(15+45*3)
=25*150
=3750
b: \(=-10\left(25+75-50\right)=-10\cdot50=-500\)
c: =>3^x-2=27
=>x-2=3
=>x=5
d: =>2x-5=-4
=>2x=1
=>x=1/2
e: =>2(x-1)^2=32
=>(x-1)^2=16
=>x-1=4 hoặc x-1=-4
=>x=-3 hoặc x=5
f: =>25(x+3)=75
=>x+3=3
=>x=0
9 - 25 = ( - 7 - x ) - ( 25 - 7 )
9 - 25 = - 7 - x - 25 + 7
9 - 25 = - x - 25
- 14 = - x - 25
=> x thuộc rỗng
11 + ( 15 - 11 ) = - 4 . x - ( 25 - 10 )
11 + 15 - 11 = - 4 . x - 25 + 10
15 = - 4 . x - 15
=> = - 4 . x
17 - { - x - ( - x ) } = - 1
17 + x + x = - 1
17 + 2x = - 1
2x = - 1 - 17
2x = - 18
x = - 18 : 2
x = - 9
=> - x = 9
x + { ( x + 3 ) - [ ( x + 3 ) - ( - x - 2 )]} = x
x + { x + 3 - [ x + 3 + x + 2 ]} = x
x + x + 3 - x - 3 - x - 2 = x
x - x - 2 = 2
x - 2 = 2 - x
=> x = 0
\(x\left(x-2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x-2=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=2\end{cases}}\)
\(\left(x+1\right)+\left(x+2\right)+...+\left(x+10\right)=25\)
\(\Rightarrow\left(x+x+...+x\right)+\left(1+2+...+10\right)=25\)
\(\Rightarrow10x+105=25\)
\(\Rightarrow10x=-80\)
\(\Rightarrow x=-8\)
Vậy x = -8
(x + 1) + (x + 2) + ... + (x + 9) + (x + 10) = 25
x + 1 + x + 2 + ... + x + 9 + x + 10 = 25
10x + (1 + 2 + ... + 9 + 10) = 25
10x + 55 = 25
10x = 25 - 55
10x = -30
x = -3
1) 9-25=(7-x)-(25+7)
(7-x)-(25+7)=9-25
(7-x)-(25+7)=-16
(7-x)-32=-16
7-x=-16+32
7-x=16
x=7-16
x=-9
2) (27-514) -(486-73)+x=7
(27-514) -(486-73)+x=7
-487-413+x=7
-1011+x=7
x=7-(-1011)
x=7+1011
x=1018
3) 25+5+37-25+6-29-x=37
25+5+37-25+6-29-x=37
67-25+6-29-x=37
42+6-29-x=37
48-29-x=37
19-x=37
x=19-37
x=-18
4) 14+(-12)+x =10-/-15/+ /-3/
14+(-12)+x =10-15+3
14+(-12)+x =-5+3
14+(-12)+x =-2
2+x=-2
x=-2-2
x=-4
Tìm x biết
a) (x-1/2)^2=4
b) 10/1/2-(x+1/3)^2=1/1/2
c) (x-1/5)^2+17/25=26/25
d) 1/5/27+(3x-7/9)^3=24/27
a) (x - 1/2)2 = 4
<=> (x - 1/2)2 = 22
<=> x - 1/2 = -2; 2
<=> x - 1/2 = 2 hoặc x - 1/2 = -2
x = 2 + 1/2 x = -2 + 1/2
x = 5/2 x = -3/2
=> x = 5/2 hoặc x = -3/2
b) 10/1/2 - (x + 1/3)2 = 1/1/2
<=> -(x + 1/3)2 = 1/1/2 - 10/1/2
<=> -(x + 1/3)2 = 1/2 - 5
<=> -(x + 1/3)2 = -5.2 + 1/2
<=> -(x + 1/3)2 = -9/2
<=> (x + 1/3)2 = 9/2
<=> x + 1/3 = \(\sqrt{\frac{9}{2}}\) hoặc x + 1/3 = \(-\sqrt{\frac{9}{2}}\)
x = \(\frac{3\sqrt{2}}{2}\) - 1/3 x = \(-\frac{3\sqrt{2}}{2}\) -1/3
=> x = \(\frac{3\sqrt{2}}{2}\) - 1/3 hoặc x = \(-\frac{3\sqrt{2}}{2}\) -1/3
c) (x - 1/5)2 + 17/25 = 26/25
<=> (x - 1/5)2 = 26/25 - 17/25
<=> (x - 1/5)2 = (3/5)2
<=> x - 1/5 = -3/5; 3/5
<=> x - 1/5 = 3/5 hoặc x - 1/5 = -3/5
x = 3/5 + 1/5 x = -3/5 + 1/5
x = 4/5 x = -2/5
=> x = 4/5 hoặc x = -2/5
x+1/2.x - 25%.x = x.(1+1/2-25%) = x.1,25 = 10 => x = 10 : 1,25 = 8
\(x+\dfrac{1}{2}x-25\%x=10\\ \Leftrightarrow x+\dfrac{1}{2}x-\dfrac{1}{4}x=10\\ \Leftrightarrow\dfrac{5}{4}x=10\\ \Leftrightarrow x=8\)
=>5/4x=10
=>x=8